Analysis of Microbial Contamination in Oreochromis Niloticus in Waduk Muara Nusa Dua - Ni Kadek Peniasih; I Gede Suranaya Pandit; Dewa Gede Semara Edi (Warmadewa University Press, 2020)
This study aims to determine the microbiological contamination in the main water source of the Muara Nusa Dua Reservoir, the Tukad Badung River, and to determine the microbiological quality of fresh Oreochromis niloticus caught in the Muara Nusa Dua Reservoir in Denpasar. The study was conducted in May-August 2019 at the Denpasar Veterinary Laboratory. The method used is a descriptive method that aims to describe or describe the condition of the Tukad Badung watershed which empties into the Muara Nusa Dua Reservoir (Estuary Dam). Objective tests include the total bacterial test, the Coliform test, and the Escherichia coli contamination test. Water quality measurements are also carried out as supporting data from this study. The results of the study stated that there was microbiological contamination in the water source of the Muara Nusa Dua Reservoir, the Tukad Badung river, which also had an impact on the waters of the Muara Nusa Dua Reservoir. Microbiological contamination research results showed the microbiological quality of ten samples of Oreochromis niloticus in the form of the highest total bacteria was at 2.2x104, the highest total Coliform was 1.9x104 and the highest Escherichia coli contamination was at 93 APM / g with an average reservoir water quality Muara Nusa Dua in the form of temperature 27.3 Â°C, salinity 0.208 â€°, degree of acidity (pH) 6.5, dissolved oxygen (DO) 5,97 ppm. Organoleptic observations included the appearance, smell, and texture of Oreochromis niloticus with good results because when testing Oreochromis niloticus is still alive